Integration of Antifouling and Underwater Sound Absorption Properties into PDMS/MWCNT/SiO2 Coatings - Pan Cao; Huming Wang; Mingyi Zhu; Yifeng Fu; Chengqing Yuan (Biomimetics, 2022)
Any surface immersed in sea water will suffer from marine fouling, including underwater sound absorption coatings. Traditional underwater sound absorption coatings rely heavily on the use of toxic, biocide-containing paints to combat biofouling. In this paper, an environmentally-friendly nanocomposite with integrated antifouling and underwater sound absorption properties was fabricated by adopting MWCNTs-COOH and SiO2 into PDMS at different ratios. SEM, FTIR and XPS results demonstrated MWCNTs were mixed into PDMS, and the changes in elements were also analyzed. SiO2 nanoparticles in PDMS decreased the tensile properties of the coating, while erosion resistance was enhanced. Antibacterial properties of the coatings containing MWCNTs-COOH and SiO2 at a ratio of 1:1, 1:3, and 1:5 reached 62.02%, 72.36%, and 74.69%, respectively. In the frequency range of 1500–5000 Hz, the average sound absorption coefficient of PDMS increased from 0.5 to greater than 0.8 after adding MWCNTs-COOH and SiO2, which illustrated that the addition of nanoparticles enhanced the underwater sound absorption performance of the coating. Incorporating MWCNTs-COOH and SiO2 nanoparticles into the PDMS matrix to improve its sound absorption and surface antifouling properties provides a promising idea for marine applications.